(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
A method for treating chronic pain syndrome, spasticity, and pelvic organ dysfunction. The effect is achieved by electrical impulses delivered by electrodes implanted in the epidural space. Electrical impulses activate pain-inhibiting neurons in the posterior horn of the spinal cord, resulting in a decrease in the sensation of pain; stimulation also causes paresthesia (a feeling of soft, pleasant vibration) in the area where the pain originates and its surroundings. SCS is considered successful if more than 50% pain reduction has been achieved on a visual analogue scale. However, a 30% pain reduction is also clinically significant. Neurostimulators are implanted in over 15,000 patients worldwide each year to treat chronic neuropathic pain. Electrodes are connected to a neurostimulator, which is implanted subcutaneously. To date, conservative treatment methods do not always provide sufficient pain relief. Pharmacotherapy is usually the first and main treatment method, however. More than 50% of patients remain dissatisfied with pharmacotherapy, regardless of the drug used. Many drugs cause various side effects. Neurostimulation is an alternative treatment method for patients with NB when traditional conservative treatment methods do not produce the desired results.[1][2].